Interactive multimedia CD ROM for learning hajj as supplementary learning platform of hajj course in Malaysia / Ilinadia Jamil - Jamil, Ilinadia (2013)
This research intends to understand the methods of conventional hajj course and how courseware concept helps in order to enhance the flexibility and quality of the training. This research also wants to identify problems or issues affecting the quality of methods in current hajj course. The first chapter will explain about background, problem statement, objective, scope, significance of research limitation of the research and overview of the research.